Probing pseudoscalars with pulsar polarization data sets - Chand, K.; Mandal, S.
Recently a data set containing linear and circular polarisation information of a collection of six hundred pulsars has been released. The operative radio wavelength for the same was 21 cm. Pulsars radio emission process is modelled either with synchroton/superconducting self-Compton route or with curvature radiation route. These theories fall short of accounting for the circular polarisation observed, as they are predisposed towards producing, solely, linear polarisation. Here we invoke (pseudo)scalars and their interaction with photons mediated by colossal magnetic fields of pulsars, to account for the circular part of polarisation data. This enables us to estimate the pseudoscalar parameters such as its coupling to photons and its mass in conjunction as product. To obtain these values separately, we turn our attention to recent observation on 47 pulsars, whose absolute polarisation position angles have been made available. Except, a third of the latter set, the rest of it overlaps with the expansive former data set on polarisation type and degree. This helps us figure out, both the pseudoscalar parameters individually, that we report here.
Keywords: Astrophysics